Modelling of cool roof performance for double-skin roofs in tropical climate. (15th March 2015) - Zingre, Kishor T.; Wan, Man Pun; Wong, Swee Khian; Toh, Winston Boo Thian; Lee, Irene Yen Leng
Abstract: Double-skin roof is a popular passive cooling solution to curb heat gain into buildings and cool roof is another emerging solution. This study proposed a novel CRHT (cool roof heat transfer) model for double-skin roof which is able to model the heat transfers for a double-skin roof combined with cool roof. The CRHT model was validated against experiments performed in two identically-configured, naturally ventilated apartments in Singapore. CRHT predictions match with experimental measurements with reasonable accuracy. White-color cool coating on a flat double-skin roof reduces the daily heat gain by 0.21 kWh/m 2 (or 51%), resulting peak indoor air temperature reduction by 2.4 °C on a sunny day. Furthermore, thermal performance of cool roof is compared with double-skin roof using the CRHT model. In the roof setup of the current study, double-skin roof is about 6% more effective than cool roof in reducing annual heat gain into the apartment during day time. However, the extra insulation of double-skin roof hinders the heat loss during night time, ensuing cool roof is almost equally effective in reducing net annual heat gain. The proposed CRHT model is generally applicable to any climate conditions as demonstrated by applying it for Mediterranean climate of Athens, Greece. Graphical abstract: Highlights: CRHT (Cool roof heat transfer) model is proposed for double-skin roof + cool roof. CRHT model is precise and easy-to-apply to NV (naturally ventilated) buildings. CRHT model is validated against experiments performed in a real-scale NV building. Impact of cool roof on double-skin roof and single-skin roof are investigated. Performances of four roof cases are studied in tropical and Mediterranean climates.